P234 The effect of calcitriol on the expression of interferon signature genes in dendritic cells and macrophages in systemic lupus erythematosus. (23rd April 2022) - Magro, Rosalie; Seria, Elisa; Grech, Godfrey; Borg, Andrew A; Scerri, Christian
Abstract: Background/Aims: A number of studies have demonstrated the inverse association between vitamin D and (i) disease activity and (ii) interferon (IFN) signature gene expression in systemic lupus erythematosus (SLE). The aim of the study was to establish the effect of calcitriol supplementation to cultured macrophages and dendritic cells (DC) from a SLE patient and control, on the expression of 12 IFN signature genes, interferon regulatory factor (IRF)7 and IRF8. Methods: Blood samples were collected from a 41-year-old female SLE patient who fulfilled the SLICC classification criteria for SLE and from a 36-year-old healthy female control after obtaining informed consent. Both patients had a serum 25-hydroxyvitamin D level of 25ng/ml. Peripheral blood mononuclear cells (PBMC) were isolated by using histopaque®-1077. CD83 and CD14 expression was measured by flow cytometry and cell count and viability were assessed. The PBMC suspension was cultured in 6-well plates using: (i) ImmunoCult TM DC culture kit (following kit protocol) for DC differentiation, (ii) culture medium for macrophage differentiation containing RPMI 1640 Medium, DMEM, fetal bovine serum and LPS. Following 7 days of incubation, differentiation of cells was confirmed using microscopy and flow cytometry to measure CD83 and CD14 expression. Calcitriol at a concentration of 20nM was added to half of the wells of each sample category. Following 24 and 48 hours, RNA extraction was carried out on treated and untreated samples. QuantiGene Plex technology was used to measure the expression of 12 IFN signature genes, IRF7, IRF8 and four housekeeping genes in the extracted RNA. The normalised median florescence intensity for the 12 IFN signature genes was used to calculate the IFN score. Results: A significantly lower IFN score was noted at 24 hours in SLE patient dendritic cell and macrophage cell cultures and in control macrophage cell cultures treated with calcitriol when compared with respective untreated samples (p = 0.014, p = 0.034, p = 0.031 respectively). On comparing IRF8 expression in treated and untreated cell cultures, a significantly lower IRF8 expression was noted in treated macrophage cell cultures obtained from both SLE patient and control (p = 0.034, p = 0.041). No difference in IRF7 expression was noted in treated and untreated cultures for all samples. Conclusion: The suppression of the interferon signature genes in dendritic cell and macrophage cell cultures with vitamin D was confirmed in the in vitro experiment carried out. In this experiment a decrease in the expression of IRF8 (known to have a VDR binding site) was also observed in macrophage cultures from both SLE patient and control. Disclosure: R. Magro: None. E. Seria: None. G. Grech: None. A.A. Borg: None. C. Scerri: None.